Definitive radiotherapy vs. postoperative radiotherapy for lower gingival carcinomas of the mandible: a asingle-center report about outcome and toxicity - Uzun-Lang, Kristin; Akbaba, Sati; Held, Thomas; Kargus, Steffen; Horn, Dominik; Bougatf, Nina; Bernhardt, Denise; Freier, Kolja; Rieken, Stefan; Debus, Jürgen; Adeberg, Sebastian (Strahlentherapie und Onkologie, 2019)
Purpose To assess radiotherapy (RT) outcomes in patients with gingival carcinoma and growth up to or involvement of the lower jaw bone. Methods This was a retrospective analysis of 51 patients with squamous cell carcinomas of the gingiva. Patients received deﬁnitive (group 1, 31.4%) or postoperative (group 2, 66.7%) RT between 2005 and 2017 at the Department of Radiation Oncology, University Hospital Heidelberg. The primary endpoint was overall survival (OS) in both treatment groups. Other endpoints were local-disease-free survival (LDFS), progression-free survival (PFS) and treatment-related toxicity (Common Terminology Criteria for Adverse Events, CTCAE, Version 4.03).
Gesehen am 19.11.2019